Irreversible Electroporation of Malignant Hepatic Tumors--Alterations in Venous Structures at Subacute Follow-Up and Evolution at Mid-Term Follow-Up. - Marco Dollinger; René Müller-Wille; Florian Zeman; Michael Haimerl; Christoph Niessen; Lukas P Beyer; Sven A Lang; Andreas Teufel; Christian Stroszczynski; Philipp Wiggermann (PLoS ONE, 2015)
To evaluate risk factors associated with alterations in venous structures adjacent to an ablation zone after percutaneous irreversible electroporation (IRE) of hepatic malignancies at subacute follow-up (1 to 3 days after IRE) and to describe evolution of these alterations at mid-term follow-up.43 patients (men/women, 32/11; mean age, 60.3 years) were identified in whom venous structures were located within a perimeter of 1.0 cm of the ablation zone at subacute follow-up after IRE of 84 hepatic lesions (primary/secondary hepatic tumors, 31/53). These vessels were retrospectively evaluated by means of pre-interventional and post-interventional contrast-enhanced magnetic resonance imaging or computed tomography or both. Any vascular changes in flow, patency, and diameter were documented. Correlations between vascular change (yes/no) and characteristics of patients, lesions, and ablation procedures were assessed by generalized linear models.191 venous structures were located within a perimeter of 1.0 cm of the ablation zone: 55 (29%) were encased by the ablation zone, 78 (41%) abutted the ablation zone, and 58 (30%) were located between 0.1 and 1.0 cm from the border of the ablation zone. At subacute follow-up, vascular changes were found in 19 of the 191 vessels (9.9%), with partial portal vein thrombosis in 2, complete portal vein thrombosis in 3, and lumen narrowing in 14 of 19. At follow-up of patients with subacute vessel alterations (mean, 5.7 months; range, 0 to 14 months) thrombosis had resolved in 2 of 5 cases; vessel narrowing had completely resolved in 8 of 14 cases, and partly resolved in 1 of 14 cases. The encasement of a vessel by ablation zone (OR = 6.36, p<0.001), ablation zone being adjacent to a portal vein (OR = 8.94, p<0.001), and the usage of more than 3 IRE probes (OR = 3.60, p = 0.035) were independently associated with post-IRE vessel alterations.Venous structures located in close proximity to an IRE ablation zone remain largely unaffected by this procedure, and thrombosis is rare.